Manual de funciones para los colaboradores de la Empresa MIDASOLUTIONS S.A - Solís Rodríguez, Lorena Lucia (2024)
A Roles and Functions Manual, also known as a Job Description Manual, is a compendium that details the responsibilities, tasks and functions inherent to various positions or divisions in a company. This document provides a comprehensive breakdown of the tasks, duties and expectations related to each job position. The main purpose of a Roles and Functions Manual lies in ensuring transparency and uniformity in job descriptions, establishing a shared understanding of hierarchy and responsibilities in the organization. This manual serves as an essential reference point for employees, managers and the human resources team, providing a clear framework for evaluating performance, setting job requirements and outlining career paths.....